Antioxidative effect of astragalosides on acute pancreatitis in mice - Hou, Xueting; Yu, Miao; Xu, Yang; Wang, Liuwei; Chen, Yishan; Tao, Ruisong; Zhang, Qixin; Zhu, Yong (Frontiers in Veterinary Science, 2024)
The research examined the antioxidative impact of astragalosides (AST) on experimental acute pancreatitis (AP) in mice. Further exploration of AST's antioxidative effect on AP was conducted through antioxidant therapy experiments on an acute pancreatitis mouse model. The AP model in mice was induced by retrograde injection of sodium deoxycholate into the biliary and pancreatic ducts. Serum amylase activity was monitored at various time points following induction. Furthermore, 24 hours post-induction, levels of serum nitric oxide (NO), superoxide dismutase (SOD) activity, and malondialdehyde (MDA) content in pancreatic tissue were assessed. Treatment with three doses of AST (20, 40, 80 mg/kg) resulted in reduced serum amylase activity in model mice, improvement in histopathological injuries in pancreatic tissue, normalization of elevated serum NO levels, increased SOD activity, and decreased MDA production. In conclusion, these findings suggest that AST enhances recovery in an experimental acute pancreatitis mouse model by exerting antioxidative effects.